The heme-copper oxidases of Thermus thermophilus catalyze the reduction of nitric oxide: Evolutionary implications - Giuffrè, Alessandro (The National Academy of Sciences, 1999)
We show that the heme-copper terminal oxidases of Thermus thermophilus (called ba(3) and caa(3)) are able to catalyze the reduction of nitric oxide (NO) to nitrous oxide (N(2)O) under reducing anaerobic conditions. The rate of NO consumption and N(2)O production were found to be linearly dependent on enzyme concentration, and activity was abolished by enzyme denaturation. Thus, contrary to the eukaryotic enzyme, both T. thermophilus oxidases display a NO reductase activity (3.0 ± 0.7 mol NO/mol ba(3) × min and 32 ± 8 mol NO/mol caa(3) × min at [NO] ≈ 50 μM and 20°C) that, though considerably lower than that of bona fide NO reductases (300–4,500 mol NO/mol enzyme × min), is definitely significant. We also show that for ba(3) oxidase, NO reduction is associated to oxidation of cytochrome b at a rate compatible with turnover, suggesting a mechanism consistent with the stoichiometry of the overall reaction. We propose that the NO reductase activity of T. thermophilus oxidases may depend on a peculiar Cu(B)(+) coordination, which may be revealed by the forthcoming three-dimensional structure. These findings support the hypothesis of a common phylogeny of aerobic respiration and bacterial denitrification, which was proposed on the basis of structural similarities between the Pseudomonas stutzeri NO reductase and the cbb(3) terminal oxidases. Our findings represent functional evidence in support of this hypothesis.